Volatile compounds in off-odor honey - Bruno Rafael da Silva; Carlos D’Apolito; Sílvia Carvalho Campos Botelho; Larissa Cavalheiro; Ednaldo Antônio de Andrade; Carmen Wobeto (Ciência Rural, 2021)
ABSTRACT: Climatic conditions in the mid-northern region of Mato Grosso State in Brazil are favorable for beekeeping. However, since 2011, the honey production chain has suffered losses because the production of off-odor honey has made it impossible to market the honey. Reports from beekeepers indicated a relationship between the off-odor in the honey and the nectar of Borreria verticillata (L.) G. Mey (Rubiaceae). In this study, the botanical origins and volatile profiles of ten off-odor honeys (H1-H10) and flowers of B. verticillata were evaluated. Palynological and sensorial analyses of the honeys were performed; a scale from 1 to 4 was applied for the sensorial analysis, in which 1 indicates no off-odor and 4 indicates extreme off-odor. Analysis of volatile was performed by using headspace solid-phase microextraction and gas chromatography-mass spectroscopy methods. The honeys investigated were classified with very high to intense off-odors, except H4 and H5, which did not differ from the control honey (no off-odor). Palynological analyses showed that honeys H1-H4, H7, and H9 were monofloral from B. verticillata, whereas in H5, H6, H8, and H10 this pollen were accessory. However, there was no quantitative correlation between the B. verticillata pollen content and the off-odor attributes of the honeys. Skatole was identified in all of the honeys except H4, H5, and the control honeys, suggesting that skatole contributed to the off-odor attributes of the products. However, further studies are required to investigate the origin of the skatole because it is not transferred directly from B. verticillata flowers to the honey.